The role of RNA structural motifs in RNA-lipid raft interaction - Rafał Mańka; Karolina Sapoń; Joanna Zaziąbło; Teresa Janas; Aleksander Czogalla; Tadeusz Janas (Scientific Reports, 2025)
Abstract Here, we sought to determine the role of specific RNA structural motifs in the interaction of RNA with model lipid vesicles containing liquid-ordered domains (RAFT liposomes). We show that the presence of several small apical loops within RNA structure favors RNA affinity for RAFT liposomes while the increased number of nucleotides within bulges inhibits this affinity. FRET flow cytometry measurements confirmed a modulation of the interaction of RNA with plasma membrane by the presence of specific RNA structural motifs. The analysis of viral RNA fragments revealed that a long double helix at the apical loop increases the affinity of viral RNA to lipid rafts. The analysis of exosomal Y RNAs secreted by nematode parasites showed that the presence of the EXO-motif GGAG is strongly correlated to the presence of small number of large apical loops within RNA structure. These results show that RNA structural motifs can modulate RNA affinity to liquid-ordered membrane lipid raft domains thus suggesting the importance of these motifs both for the mechanism of RNA loading into extracellular vesicles, and for the development of RNA-based lipid biosensors for monitoring of viral RNAs in biofluids and wastewater.